Pengaruh Norma Subjektif dan Kewajiban Moral terhadap Kepatuhan Wajib Pajak dimediasi Sikap Wajib Pajak : Studi Pada Wajib Pajak Kendaraan Bermotor di Kota Surabaya - Nanda Pinandita Ramadhani; Siti Mujanah; Achmad Yanu Alif Fianto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Taxes are a source of state financing and a regulatory tool in implementing government policies. This research investigates the influence of Subjective Norms and Moral Obligations on Taxpayer Attitudes. Also investigate whether Taxpayer Attitudes are a good mediator. This study conducted a survey of motor vehicle taxpayers in the city of Surabaya. Using a purposive sampling method with the sample criteria being taxpayer respondents who are processing motor vehicle taxes in the city of Surabaya, 155 respondents. The data was then analyzed using Structural Equation Modeling. The findings show that subjective norms and moral obligations make a positive contribution to taxpayer attitudes. Research also proves that taxpayer attitudes mediate the relationship between subjective norms and moral obligations on taxpayer compliance. This study contributes to understanding taxpayer behavior by using a framework of taxpayer attitudes and taxpayer compliance with motor vehicle taxes, which can also be applied to other taxpayers.